Wasathiyah Islam In Local Language Commentaries In Indonesia: An Analysis Of Readers’ Reception Of Sundanese, Javanese, And Malay - Supardi Supardi; Adang Kuswaya; Muhammad K. Ridwan (Millati: Journal of Islamic Studies and Humanities, 2023)
This article examines the concept of Islamic Wasathiyah from the perspective of readers of Sundanese, Javanese, and Malay local commentaries. The study employed a qualitative approach, engaging readers of Al-Ibriz in Pati, Central Java, Lanyepaneun in Ciamis, West Java, and Hamka's Tafsir al-Azhar. The study revealed distinct interpretations among these groups. Javanese readers understood Islamic Wasathiyah in al-Baqarah 143 as being in the middle of religious practices. For Sundanese readers, it carried the same ‘in the middle’ connotation but with a specific focus on social life, denoting neither stinginess nor extravagance. In the Malay interpretation of Tafsir al-Azhar, it denotes the position of ummatan wasaṭan, signifying a community dedicated to upholding the straight path. The study also identifies two primary indicators of Islamic Wasathiyah, i.e., balance and fairness. According to readers of al-Ibriz, balance is interpreted as wad'u syai fi mahallihi, placing something in its proper place, while readers of Lanyepaneun emphasize being fair to oneself and others. In terms of tolerance, readers of al-Ibriz perceive it as the absence of compulsion when embracing different religions, emphasizing that the choice of truth should not be a matter of dispute. Conversely, readers of Lanyepaneun have their own interpretation of tolerance. All these interpretations are shaped by the socio-cultural contexts of the commentary authors and their readers, providing a rich tapestry of perspectives on Islamic Wasathiyah. In sum, while the Javanese, Sundanese, and Malay interpretations of 'ummatan wasaṭan' share the overarching theme of moderation, each interpretation reflects the unique cultural, historical, and linguistic contexts in which it is situated. These interpretations demonstrate the Quran's adaptability to diverse cultural settings and its ability to convey universal principles through language and context-specific nuances.